Regional shear wave elastography of Achilles tendinopathy in symptomatic versus contralateral Achilles tendons - Crawford, Scott K.; Thelen, Darryl; Yakey, Janice M.; Heiderscheit, Bryan C.; Wilson, John J.; Lee, Kenneth S. (European radiology, 2023)
Objectives Ultrasound often corroborates clinical diagnosis of Achilles tendinopathy (AT). Traditional measures assess macromorphological features or use qualitative grading scales, primarily focused within the free tendon. Shear wave imaging can non-invasively quantify tendon elasticity, yet it is unknown if proximal structures are affected by tendon pathology. The purpose of the study was to determine the characteristics of both traditional sonographic measures and regional shear wave speed (SWS) between limbs in patients with AT. Methods Twenty patients with chronic AT were recruited. Traditional sonographic measures of tendon structure were measured. Regional SWS was collected in a resting ankle position along the entire length of the tendon bilaterally. SWS measures were extracted and interpolated across evenly distributed points corresponding to the free tendon (FT), soleus aponeurosis (SA), and gastrocnemius aponeurosis (GA). Comparisons were made between limbs in both traditional sonographic measures and regional SWS. Results Symptomatic tendons were thicker (10.2 (1.9) vs. 6.8 (1.8) mm; p < 0.001) and had more hyperemia ( p = 0.001) and hypoechogenicity ( p = 0.002) than the contralateral tendon. Regional SWS in the FT was lower in the symptomatic limb compared to the contralateral limb (11.53 [10.99, 12.07] vs. 10.97 [10.43, 11.51]; p = 0.03). No differences between limbs were found for the SA ( p = 0.13) or GA ( p = 0.99). Conclusions Lower SWS was only observed in the FT in AT patients, indicating that alterations in tendon elasticity associated with AT were localized to the FT and did not involve the proximal passive tendon structures. Key Points • Baseline characteristics of a pilot sample of 20 subjects suffering from chronic Achilles tendinopathy showed differences in conventional sonographic measures of tendon thickness, qualitatively assessed hypoechogenicity, hyperemia, and quantitative measures of shear wave speed. • Regional shear wave speeds were lower in the free tendon but not in the proximal regions of the soleus or gastrocnemius aponeuroses in Achilles tendinopathy patients. • Using shear wave imaging to estimate tendon stiffness may prove beneficial for clinical validation studies to address important topics such as return to activity and the effectiveness of rehabilitation protocols.